Studies on Cellular Behaviour in Regenerative and Non-Regenerative Tissues of Dianthus Caryophyllus Linn. CV. Grenadin in a Tissue Culture System - Mat Taha, Rosna; A. Kadir, Norfariza (Malaysian Journal of Science, 2004)
In the present study, tissue culture of $Dianthus$ $caryophyllus$ (Carnation) was initiated from various explants. Stem and shoot explants could give rise to complete plants when cultured on MS medium supplemented with 2.0 mg/l NAA, whilst leaf and root explants failed to regenerate, but only managed to produce roots, when cultured on the same medium. Regenerative tissues are tissues which are capable of giving rise to complete plants, while tissues which failed to regenerate are considered nonÃ‚Â¬regenerative. In this paper, some cellular activities, such as Mitotic Index (MI), chromosome counts, cell doubling times (Cdt), nuclear DNA content and mean cell and nuclear areas were examined in these tissues to compare and contrast between these two types of tissues. Our results showed that, the cell doubling time was faster and the nuclear to cell area ratios were constant in regenerative tissues, whereas, other parameters were almost similar in both tissue types. $Dianthus$ $caryophyllus$ was found to be stable when their cells were brought into culture system indicating that clonal propagation is highly achievable with this spesies. Although the occurrence of polyploidy was very high in regenerative tissues after 3 weeks, 2 months and 3 months in culture, complete plant regeneration could still be accomplished.